Self-efficacy as a moderator of information-seeking effectiveness. - Brown, Steven P.; Ganesan, Shankar; Challagalla, Goutam (Journal of Applied Psychology, 2001)
The authors assessed previously unexplored processes by which information seeking and self-efficacy contribute to self-regulatory effectiveness in industrial selling. They assessed the synergistic interaction of inquiry and monitoring with respect to role clarity and tested whether this interaction was further moderated by self-efficacy. Results indicated that the role-clarifying effects of feedback inquiry and monitoring were contingent rather than independent. Role clarity increased as the combination of inquiry and monitoring increased. Furthermore, these joint effects were moderated by self-efficacy, such that high-self-efficacy employees were able to effectively use the combination of inquiry and monitoring to clarify role expectations, whereas low-self-efficacy employees were not. Implications for theory, practice, and future research are discussed.